Effectiveness of Calcium Hydroxide and Gingerols Mixture as a Novel Obturation Material for Infected Root in Primary Teeth: A Randomized Clinical Trial - Fathi A. Qasem; Salwa M. Awad; Rizk A. Elagamy (Hindawi Limited, 2024)
Introduction. The tendency to use dental materials of plant origin is one of the prevailing trends in dentistry to reduce exposure to materials that could have some toxic impact in the long term. Objective. To evaluate the efficacy of calcium hydroxide combined with gingerols (Ginge-Cal) as a novel obturation material for treating infected primary teeth and decreasing the recurrence of infection. Materials and Methods. The study was conducted on 30 lower primary molars with infected pulp for children aged 4-8 years. The sample was randomly divided into two groups depending on the tested obturation material: Ginge-Cal group and the Metapex group. The evaluation was done by different parameters clinically and radiographically at various intervals up to 12 months. Results. Based on chi-squared and McNamara's test with a 5% significance level, the clinical results indicated that Ginge-Cal group was more effective than the Metapex group in reducing or eliminating pain (P=0.467) after 1 week, sensitivity to percussion (P=0.090) at 3 months of follow-up, purulent swelling (P=0.444) at 6 and 9 months of follow-up, fistula, and tooth mobility. The radiographic results, based on the periapical and furcation area radiolucency at 12 months of follow-up, favored Ginge-Cal group over the Metapex group (P=0.683), (P=0.456), respectively. There were no statistically significant differences in pathological root resorption and periodontal space. The differences within the Ginge-Cal group were directly influenced by the time intervals in a statistically significant manner, ranging from (P=0.004) to (P<0.001). The success percentage was 87.5% for Ginge-Cal group and 64.3% for Metapex group. Conclusions. Ginge-Cal can be considered a promising material for treating the infected root canal when used as an obturation material for the infected root canal. This trial is registered with NCT05181813.